Refractory seizures with encephalopathy may be due to Hashimoto encephalopathy - Atraya Samanta; Agniva Deb; Indranil Karmakar; Santanu Roy (Wolters Kluwer Medknow Publications, 2023)
Background: Hashimoto's encephalopathy, also known as steroid-responsive encephalopathy associated with autoimmune thyroiditis, is a relatively uncommon neurological disorder, mostly in adults, with an extremely rare occurrence in children. Clinical Description: A 9-year-old girl presented with unprovoked seizures and encephalopathy. She had been diagnosed with hypothyroidism, at around 6 ½ years of age, though was noncompliant to therapy with levothyroxine. Management: The child was managed with intravenous (IV) antiepileptics and other supportive care. Seizures were refractory and with worsening sensorium, she required mechanical ventilation. The magnetic resonance imaging of the brain was unremarkable, as also the cerebrospinal analysis. Autoimmune encephalitis panel was negative. The electroencephalogram showed background activity of 10-11 Hz and few areas with generalized slow waves. As she was a known case of hypothyroidism without taking thyroid supplements for the past few months, thyroid profile was sent. Reports showed FT3-1.1 pg/dL, FT4-0.515 ng/dL, and thyroid-stimulating hormone (TSH) - 107.3 μIU/mL. Thyroid antibody profile revealed antithyroid peroxidase antibody >500 IU/mL and antithyroglobulin antibody >1000 IU/mL. Following this, an ultrasound of the neck was done which showed features of thyroiditis. Considering the possibility that the underlying thyroiditis could explain the obtunded state and refractory seizures, the patient was started on levothyroxine and IV methylprednisolone. The sensorium of the child improved dramatically, and she got extubated. There were no further seizures and her TSH level reduced gradually and eventually, she was discharged. Conclusions: In a child with altered sensorium and refractory seizures, Hashimoto encephalopathy is a diagnosis of exclusion and may be considered when most of the common causes of encephalopathy and seizures have been ruled out, especially in the setting of some clinical clues of hypothyroidism. The condition is often reversible with good response to steroid therapy.